2015
DOI: 10.1084/jem.20150354
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial CD99 signals through soluble adenylyl cyclase and PKA to regulate leukocyte transendothelial migration

Abstract: CD99 is a critical regulator of leukocyte transendothelial migration (TEM). Watson et al. describe the CD99 signaling pathway responsible. This involves a complex of CD99 with the A-kinase anchoring protein ezrin and soluble adenylyl cyclase that activates protein kinase A during leukocyte TEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(128 citation statements)
references
References 64 publications
3
124
0
Order By: Relevance
“…This results in chemokine and cytokine release by various cell types followed by inflammation close to the site of injury. diapedesis of monocytes, neutrophils and T-cells was established 104,105 making this junctional protein of interest in the context of unraveling the initial receptor involved in formatting of a confined actin pore during leukocyte TEM. Intracellular CD99 signaling regulating leukocyte TEM has recently been described to involve soluble adenylyl cyclase (sAC) that activates protein kinase A (PKA).…”
Section: Junctional Protein Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in chemokine and cytokine release by various cell types followed by inflammation close to the site of injury. diapedesis of monocytes, neutrophils and T-cells was established 104,105 making this junctional protein of interest in the context of unraveling the initial receptor involved in formatting of a confined actin pore during leukocyte TEM. Intracellular CD99 signaling regulating leukocyte TEM has recently been described to involve soluble adenylyl cyclase (sAC) that activates protein kinase A (PKA).…”
Section: Junctional Protein Candidatesmentioning
confidence: 99%
“…This activation occurs at the lysine-rich intracellular tail of CD99 using the A-kinase anchoring protein (AKAP) ezrin as a scaffold. 104 Involvement of ezrin in this signaling complex could connect homophilic CD99 interaction to formation of the F-actin rich pore, because ezrin belongs to the ERM family (ezrin/ radixin/moesin) of proteins that link actin filaments to the plasma membrane. Moreover, CD99 functions at a later stage during the diapedesis step, i.e., when the leukocyte has worked its way into the junction already.…”
Section: Junctional Protein Candidatesmentioning
confidence: 99%
“…The findings reported here give us new insights into the mechanisms leading to expression of CD1a on human DCs and the critical role of CD99 transmembrane molecule in this expression. We describe here a new function for the CD99 molecule aside from its role in the regulation of the expression of MHC class I [32]. Here we report that CD99 is involved through a distinct mechanism in the regulation of CD1a through its transcription.…”
Section: Discussionmentioning
confidence: 82%
“…The mRNA of CD99 is expressed as two isoforms, a long form of 185 amino acids (CD99LF) and a short form of 161 amino acids (CD99SF) obtained by alternative splicing of the cytoplasmic region [27]. Aside from its role in the regulation of adherence, cell death and transendothelial migration [28][29][30][31][32] we previously showed that CD99 plays an active role in the transport of MHC class I molecules [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation